EDUKASI DAN PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH UNTUK MENINGKATKAN LEGALITAS DAN DAYA SAING USAHA - Soleh, Ahmad; Pudail, M; Muhibin, Ahmad; Dhiaurahman, Hernanda (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This community service program aims to enhance the legality and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) through education and assistance in obtaining the Business Identification Number (Nomor Induk Berusaha/NIB). The program was conducted in May 2025 in Tegowanu, Kaliagung, Kulon Progo Regency, Yogyakarta, where 31 potential but unlicensed MSMEs were identified. The method employed was Asset-Based Community Development (ABCD), which optimized local human resources—specifically the youth organization (Karang Taruna)—as technological facilitators to help MSME owners overcome barriers within the Online Single Submission (OSS) system. The results demonstrated the program's success in facilitating and assisting 12 MSME owners in independently obtaining their NIB certificates. This success confirms that asset-based intervention is effective in transforming MSMEs into legal entities and building digital self-reliance within local communities. The impact includes increased business legitimacy, readiness for capital access, and strengthened competitiveness for Tegowanu MSMEs in the modern market.